Coralliocaris junckeri, a new pontoniine shrimp species (Crustacea: Decapoda: Palaemonidae) from Futuna Island, Central Pacific - Li, Xinzheng; Poupin, Joseph (Zootaxa, 2012)
A new pontoniine shrimp species, family Palaemonidae, genus Coralliocaris Stimpson, 1860, C. junckeri sp. nov., is de-scribed based on an ovigerous female specimen from Futuna Island, Futuna Reef in the central Pacific. The new speciescan be distinguished from its congeneric counterparts by its second pereopod chelae, the fingers of the first pereopods, the unarmed rostrum and the colour pattern.